NEUROLEADERSHIP AS A PROMOTER OF MOTIVATION AND ENGAGEMENT IN COMPANIES - Barros Gama, Cleotemberg; Bittencourt Saraiva, Waslany (Revista Gênero e Interdisciplinaridade, 2023)
The subjects of motivation and engagement in companies are the focus of several studies today. We talk, for example, about employees, competitive athletes, students and motivated or unmotivated students. In particular, in a performance- and results-oriented capitalist world, there is endless interest in how people can be motivated to work for other people’s goals and at the same time "perform well." This study seeks to answer the guiding question: what are the influences of Neuroscience through Neuroleadership as a motivation and engagement factor in companies? The general objective is to analyze how Neuroleadership contributes to the processes of motivation and engagement in Organizations through correlations with Neuroscience. The methodology used was qualitative-descriptive research, based on bibliographical research where studies were evaluated using the inductive method of studies published between 2016 and 2023 relating to the topic at hand. The results found indicate that research in Neuroscience and Neuroleadership brings new knowledge about the functioning of our brain, and this applies to different worlds such as health, education, but also management and leadership. Neuroscience research brings new knowledge about how our brain works, and this applies to different worlds such as health, education, but also management and leadership. It is concluded that Neuroleadership helps to clarify the neural mechanisms underlying these different forms of motivation. Another fundamental contribution of Neuroleadership to our understanding of motivation and engagement in the workplace is the recognition that engagement is not simply a matter of job satisfaction or enjoyment. It is a complex process influenced by a variety of factors, including a sense of purpose, autonomy, mastery, and social connection.